Trí tuệ văn hóa và kết quả công việc của người lao động: Vai trò của điều chỉnh văn hóa và gắn kết công việc - Phan Quốc, Tấn; Bùi Thị, Thanh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2020)
This research examines the relationship between cultural intelligence and performance of employees through the mediating role of cross-cultural adjustment and work engagement of employees working in FDI enterprises in Ho Chi Minh’s industrial zones. Survey data was collected from 307 provincial employees working in FDI enterprises in the Industrial zones Ho Chi Minh City. The results of model testing and structural model evaluation show that hypotheses are accepted, in which, cultural intelligence has a strong positive impact on work engagement and performance of employees; meanwhile cultural intelligence has a lower positive impact on cross-cultural adjustment, as well as cultural adjustment has a weak impact on performance; cultural adjustment and work engagement play a mediating role in the relationship between cultural intelligence and employee performance. The study also found that there is a difference between men and women, professional qualifications, and seniority in the relationship between cultural intelligence and employee performance as well as there is a difference in professional qualifications and seniority in the relationship between work engagement and employee performance at FDI enterprises in Ho Chi Minh City’s industrial zones.